A Study of Microstructure of Steel Slags Used for Pollutants Adsorption and Removal in Waste Water - Trang, Tran Thi Thu; Huu Long, Tran; Tien Dung, Pham; Hoang Tung, Vo; Xuan Sang, Nguyen; Thi Nuong, Nguyen (VNU Journal of Science: Earth and Environmental Sciences; Vol 34 No 4DO - 10.25073/2588-1094/vnuees.4245, 2018)
Abstract: "Waste treatments waste" – the reuse of waste could bring a number of environmental and economical benefits such as reducing waste and treatment cost in many industrial sectors. This study made use of steel slag as treatment material for polluted waste. High performance of fill teration may come with the parameters of volumetric mass density of steel slag is 3.1 ~ 3.6 g/cm 3 , standard screen is 0.175 mm, weight density powder is about 0.174g/cm 3 , surface is about 0.32 m 2 /g, average size is 5.3 nm. Chemical components of steel slag analyzed by XRF (X-ray fluorescence spectrometer), which shows CaO is the main component of steel slag, 48.2% and 42.5% were steel slag and steel slag powder, respectively. The following major components are Fe 2 O 3 and MgO content. Metals content determined by TCLP (Toxicity Characteristic Leaching Procedure) that shows Pb, Hg, Cd, Cr, As, Ni, Cu, Mn, Zn content which is less than National Standard II (GB 3838-2002); structure of steel slag analyzed by SEM (Scanning Electron Spectroscopy) and XRD (X-Ray diffraction) which shows include magnetite, tri-calcium silicate (Ca 3 S), di-calcium silicate (Ca 2 S), and iron in tin (FeO). Arsenic absorption and removal by steel slag are simple and possibly experimental and that can apply in large-scale so any effective from that point efficient. Keywords: Waste treatment waste, steel slag, toxic, wastewater, absorption. References [1] Liu Jiajuan, Zhao Ying, Fan Qingru, 2012. Different extraction methods influence the leaching of heavy metals in fly ash[J]. Water Supply and Drainage, 38(1):168-171. [2] Sun Huiyan, Liu Xixiu, Zhang Yunbo, 2006. ICP Simultaneous determination of chemical composition in steel slag [J]. Hebei Metallurgy, 2006, 4: 023. [3] Meng Qingsen, Shi Zongli, Wang Shunhua, 2008. Surface Modification of Attapulgite and Its Application in Wastewater Treatment [J]. Silicate Notification, 27(5): 996-999. [4] Qu D, Wang J, Hou D, et al, 2009. Experimental study of arsenic removal by direct contact membrane distillation[J]. Journal of hazardous materials, 163(2): 874-879. [5] Pokhrel D, Viraraghavan T, 2009. Biological filtration for removal of arsenic from drinking water[J]. Journal of environmental management, 90(5): 1956-1961. [6] Li Jipeng, Fang Honghui, Wang Yue, et al, 2010. Slag microstructural characteristics of different analytical approach[J]. Metallurgical environmental protection (1): 12-15. [7] Chen Xiao, Hou Wenhua, Wang Qunhui, 2009. Effect of removal Cu2+, Cd2+ and Pb2+ by furnace steel slag[J]. Environmental Scienc, 30(10):2941-2945. [8] Xue Fangbin, Song Huiping, Shi Yonglin, et al, 2013.Modified slag treatment simulation of COD wastewater [J]. Shanxi University (Natural Science), 36(3): 484-490. [9] Cheng Fangqin, Gao Rui, Song Huiping, 2012. Modified steel slag processing low ammonia nitrogen wastewate[J]. Environmental Engineering, 11(6):4027-433. [10] Ren J L, Zhang J, Li D D, et al, 2010.Behavior of dissolved inorganic arsenic in the Yellow Sea and East China Sea[J]. Deep Sea Research Part II: Topical Studies in Oceanography, 57(11): 1035-1046. [11] Zhao Haiyin, Yu Qiujun, Wei Jiangxiong, et al, 2010. Slag mineral composition, morphology and gelling activity factors [J]. Wuhan TechnologyUniversity (15): 22-26. [12] Zhang Yushu, Lei Yunbo, Li Junguo, et al 2011.Ore slag phase composition and microstructure morphology analysis [J], Metallurgical Analysis 31 (9): 11-17. [13] Deng Yanxi, Tenghaobo, Gu Haihong, Chou Rongliang, 2011. Effect of multi-metal composite contaminated soil improving effect of heavy metals in the slag and rice absorb administered [J]. Agricultural Environmental Science. 30(3): 455-460. [14] Shu Xingwu, 2007. Slag characteristics and utilization technology [J]. Nonferrous Metals Engineering and Research, 28 (5): 31-34. [15] Fang Linchuan, Huang Qiaoyun, Cai Peng, et al, 2008. Application of XAFS Technology in Heavy Metal Interface Adsorption[J]. Journal of Applied and Environmental Biology, 14(5): 737-744. [16] Hou Guihua, Li Weifeng, Guo Wei, et al, 2009. With backscattered electron image of a scanning electron microscope analysis of converter slag mineral phase [J] Materials Review, 22 (8): 208-211. [17] Singh D B, Prasad G, Rupainwar D C, 1996. Adsorption technique for the treatment of As (V)-rich effluents[J]. Colloids and Surfaces A: Physicochemical and Engineering Aspects, 111(1): 49-56. [18] Liu S Y, Gao J, Yang Y J, et al, 2010. Adsorption intrinsic kinetics and isotherms of lead ions on steel slag[J]. Journal of hazardous materials, 173(1): 558-562. [19] Liu Shengyu, Ma Shaojian, Gao Jin, et al, 2008. Research of Adsorption Mechanism of Steel Slag[J].Journal of Environmental Engineering, 2(1): 115-119. [20] Zou Xingfang, 2014. Discussion on the Relationship between Microstructure of Slag and Grinding and Sintering Performance[J]. Building Materials Development Guide, 12(4): 50-54. [21] Waslenchuk D G, 1978. The budget and geochemistry of arsenic in a continental shelf environment[J]. Marine Chemistry, 7(1): 39-52. [22] Zhang Zhaohui, Liao Jielong, Ju Jiantao, et al, 2013.Steel slag treatment process and the use of technology at home and abroad[J] Iron and Steel Research, 25(7):1-4 [23] Fishbein L, 1984. Overview of analysis of carcinogenic and/or mutagenic metals in biological and environmental samples I. Arsenic, beryllium, cadmium, chromium and selenium[J]. International journal of environmental analytical chemistry, 17(2): 113-170. [24] Ferguson J F, Gavis J, 1972. A review of the arsenic cycle in natural waters[J]. Water research, 6(11): 1259-1274. [25] Alexander Heußner, 2007. Semantic Foundation of Diagrammatic Modelling Languages Applying the Pictorial Turn to Conceptual Modelling. 215 [26] Cullen W R, Reimer K J, 1989. Arsenic speciation in the environment[J]. Chemical Reviews, 89(4): 713-764. [27] Makris K C, Sarkar D, Parsons J G, et al, 2009.X-ray absorption spectroscopy as a tool investigating arsenic (III) and arsenic (V) sorption by an aluminum-based drinking-water treatment residual[J]. Journal of hazardous materials, 171(1): 980-986. [28] Spiteri C, Slomp C P, Tuncay K, et al, 2008. Modeling biogeochemical processes in subterranean estuaries: Effect of flow dynamics and redox conditions on submarine groundwater discharge of nutrients[J]. Water resources research, 44(2). 24-30. [29] Singh T S, Pant K K, 2004. Equilibrium, kinetics and thermodynamic studies for adsorption of As (III) on activated alumina[J]. Separation and Purification Technology, 36(2): 139-147. [30] http://hyperphysics.phy-astr.gsu.edu/hbase/quantum/bragg.html [31]http://english.mep.gov.cn/standards_reports/standards/water_environment/quality_standard/200710/W020061027509896672057.pdf [32] Lenoble V, Laclautre C, Deluchat V, et al, 2005. Arsenic removal by adsorption on iron (III) phosphate[J]. Journal of hazardous materials, 123(1): 262-268. [33] Yamada H, Kayama M, Saito K, et al, 1986.A fundamental research on phosphate removal by using slag[J]. Water research, 20(5): 547-557. [34] Yu Jian, Liang Wenyan, Wang Li, et al, 2012. Adsorption Removal of Phosphorus from Wastewater by Modified Steel Slag Particles [J]. ournal of Safety and Environment, 12(006): 66-71. [35] Duan Jinming, Lin Jinmei, Fang Hongda, etc, 2012. Study on Adsorption Characteristics of Ammonia Nitrogen and Phosphorus by Modified Steel Slag [J]. Journal of Environmental Engineering, 6(1): 201-205. [36] Zhang Zhaohui, Liao Jielong, Ju Jiantao, et al, 2013.Steel slag treatment process and the use of technology at home and abroad[J] Iron and Steel Research, 25(7):1-4. [37] Chakravarty S, Dureja V, Bhattacharyya G, et al, 2002. Removal of arsenic from groundwater using low cost ferruginous manganese ore[J]. Water research, 36(3): 625-632. [38] Jha V K, Kameshima Y, Nakajima A, et al, 2008.Utilization of steel-making slag for the uptake of ammonium and phosphate ions from aqueous solution[J]. Journal of hazardous materials, 156(1): 156-162. [39] Ortiz N, Pires M A F, Bressiani J C, 2001. Use of steel converter slag as nickel adsorber to wastewater treatment[J]. Waste Management, 21(7): 631-635. [40] Gong Y, Chou H N, Tu C, et al, 2009. Effects of arsenate on the growth and microcystin production of Microcystis aeruginosa isolated from Taiwan as influenced by extracellular phosphate[J]. Journal of applied phycology, 21(2): 225-231. [41] Yang Huifen, Fu Pingfeng, Zhou Feng, 2008. Adsorption and Reduction of Cr (VI) in Water by Steel slag[J]. Proceeding of the Chinese Society Engineering, 8(3): 499-503. [42] Fishbein L, 1984. Overview of analysis of carcinogenic and/or mutagenic metals in biological and environmental samples I. Arsenic, beryllium, cadmium, chromium and selenium[J]. International journal of environmental analytical chemistry, 17(2): 113-170. [43] Lenoble V, Bouras O, Deluchat V, et al, 2002. Arsenic adsorption onto pillared clays and iron oxides[J]. Journal of Colloid and Interface Science, 255(1): 52-58. [44] Lan Y Z, Zhang S, Wang J K, et al, 2006. Phosphorus removal using steel slag[J]. Acta metallurgica sinica (English letters), 19(6): 449-454. [45] Kim D H, Shin M C, Choi H D, et al, 2008. Removal mechanisms of copper using steel-making slag: adsorption and precipitation[J]. Desalination, 223(1): 283-289. [46] Zhao Xinxin, Li Jun, Liu Yang, etc, 2006.Effect of Steel Slag on Absorption of Cadmium in Rice Soil in Liaoning Province [J]. Chinese Agricultural Science Bulletin, 22(7): 507-511. [47] Chakravarty S, Dureja V, Bhattacharyya G, et al, 2002. Removal of arsenic from groundwater using low cost ferruginous manganese ore[J]. Water research, 36(3): 625-632. [48] Ysart G, Miller P, Croasdale M, et al, 2000. UK Total Diet Study dietary exposures to aluminium, arsenic, cadmium, chromium, copper, lead, mercury, nickel, selenium, tin and zinc[J]. Food Additives & Contaminants, 17(9): 775-786.